Help-Seeking After Intimate Partner or Sexual Violence: Exploring the Experiences of International Student Women in Australia - Tran, Giang (Violence against women, 2025)
Research suggests that many international students experience intimate partner violence (IPV) or sexual violence (SV) whilst attending tertiary institutions. Yet, little is known about how they engage in help-seeking and what types of support they need following IPV/SV. In this paper, we present findings from a qualitative analysis of 30 in-depth interviews with international student women who experienced SV/IPV while studying in Australia. The findings highlight how isolation and structural factors can create significant barriers to help-seeking for international student women. Yet, the findings also highlight the agency and resourcefulness of international student women in overcoming challenges. The provision of culturally and linguistically appropriate and tailored support for international students is crucial in order to help reduce the harms of SV/IPV.